2007
DOI: 10.1002/cncr.22813
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 activation in squamous cell cancer of the oral cavity

Abstract: Thermal degradation of poly(dimethylsilylene) homopolymer (PDMS) and poly(tetramethyldisilylene‐co‐styrene) copolymer (PTMDSS) was investigated by pyrolysis‐gas chromatography and thermogravimetry (TG). PDMS decomposes by depolymerization, producing linear and cyclic oligomeric products, whereas PTMDSS decomposes by random degradation along the chain resulting in each monomeric product and various other combination products. The homopolymer was found to be much less stable than the copolymer. The decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 76 publications
4
15
1
Order By: Relevance
“…Laimer and colleagues (16) found that high levels of STAT1 in HNSCC tumor specimens correlated with improved survival in patients treated with adjuvant platinum-based chemotherapy, which is opposite the trend seen in our study. This study was similar to ours in terms of the number of patients, tumor characteristics such as anatomic subsite and stage, and method for dividing patients between high and low STAT1 staining groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Laimer and colleagues (16) found that high levels of STAT1 in HNSCC tumor specimens correlated with improved survival in patients treated with adjuvant platinum-based chemotherapy, which is opposite the trend seen in our study. This study was similar to ours in terms of the number of patients, tumor characteristics such as anatomic subsite and stage, and method for dividing patients between high and low STAT1 staining groups.…”
Section: Discussioncontrasting
confidence: 99%
“…It is unclear, however, whether specific tumor biomarkers might help identify patients more likely to benefit from the combination of cisplatin, radiation and EGFR inhibitors. Two prior small clinical studies suggest that high levels of intratumoral STAT1 might be a favorable prognostic marker for HNSCC patients treated with chemotherapy (16, 17). To explore whether STAT1 might be a biomarker of response to cisplatin and EGFR inhibition, we obtained tumor specimens from patients with advanced, high-risk HNSCC treated with surgery followed by adjuvant radiation, cisplatin and panitumumab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant activation of STAT1 has frequently been found in various cancers, such as head and neck cancer [75]. A similar STAT1 activation status was detected in patients with OSCC [76]. In this study, STAT1 displayed a significant association with OC using both the RWR-based and SP-based methods, and this molecular marker could help in guiding diagnostic and therapeutic decisions in patients with OC.…”
Section: Discussionsupporting
confidence: 62%
“…Increased STAT1 expression and high STAT1 activation (p-STAT1 protein levels) were related to a favorable prognosis in colorectal carcinoma [10,11], oral squamous cell carcinoma [12], as well as in breast cancer [13]. In addition, Sun et al [14] observed that overexpression of STAT1 was inversely related to malignant behaviors (lymph node metastasis, tumor dedifferentiation, advanced stage) of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%